EDUKASI PENTINGNYA PENGGUNAAN SUPLEMEN KESEHATAN PADA ANAK-ANAK - Alfayzah, Faradillah; Utari, Widi Gustita; Junaida, Alfini; Pratama, Muhammad Imran Ade (Jurnal Wicara, 2024)
As time goes by, there will be several lifestyle changes, one of which is people's consumption patterns. The widespread use of health supplements is one of the many things that has changed in people's consumption patterns. However, some people who consume health supplements only follow the times, without knowing the indications of these health supplements. In fact, health supplements are basically consumed to support nutritional deficiencies or strengthen a weak immune system, not as a substitute for the main nutrients that we should get from food. In addition, knowledge about health supplements is very dependent on age, so children still have quite poor knowledge about food supplements